2018
DOI: 10.1096/fj.201701384r
|View full text |Cite
|
Sign up to set email alerts
|

3D uniaxial mechanical stimulation induces tenogenic differentiation of tendon‐derived stem cells through a PI3K/AKT signaling pathway

Abstract: The tendon is a mechanosensitive tissue, but little is known about how mechanical stimulation selectively signals tenogenic differentiation and neo-tendon formation. In this study, we compared the impact of uniaxial and biaxial mechanical loading on tendon-derived stem cells (TDSCs). Our data show that there are variations in cell signaling and cell differentiation of mouse TDSCs in response to uniaxial and biaxial loading in monolayer culture. Whereas uniaxial loading induced TDSCs toward tenogenic and osteog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 45 publications
(50 reference statements)
3
68
0
1
Order By: Relevance
“…Although biaxial loading had a clear effect, these genes are not tendon‐specific. In contrast, direct comparison of uniaxial and biaxial stimuli showed that uniaxial loading of TSPCs was more strongly pro‐tenogenic (and osteogenic) than biaxial loading, which induced a mixed osteogenic, adipogenic, and chondrogenic fate in TSPCs . Uniaxial loading of three‐dimensional (3D) TSPC constructs significantly enhanced tendon differentiation, mechanical properties, and neo‐tendon formation .…”
Section: Mechanical Stimulation and 3‐dimensional Tspc Culturementioning
confidence: 97%
See 2 more Smart Citations
“…Although biaxial loading had a clear effect, these genes are not tendon‐specific. In contrast, direct comparison of uniaxial and biaxial stimuli showed that uniaxial loading of TSPCs was more strongly pro‐tenogenic (and osteogenic) than biaxial loading, which induced a mixed osteogenic, adipogenic, and chondrogenic fate in TSPCs . Uniaxial loading of three‐dimensional (3D) TSPC constructs significantly enhanced tendon differentiation, mechanical properties, and neo‐tendon formation .…”
Section: Mechanical Stimulation and 3‐dimensional Tspc Culturementioning
confidence: 97%
“…Another strategy to induce tenogenic differentiation, while preventing phenotypic drift of TSPCs, is to expose cells to mechanical cues similar to those experienced in the native microenvironment. 93,94 Although specific tendons undergo specific loading depending on anatomical location, the general type of loading for most tendons is uniaxial tension. To determine the effects of mechanical conditioning on TSPCs, cells are typically subjected to uniaxial or biaxial cyclic strain.…”
Section: Mechanical Stimulation and 3-dimensional Tspc Culture Dynamimentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence-activated cell sorting was conducted to identify TDSCs ( Fig. 2A) before following experiments (positive for CD90 and CD44, and negative for CD34 and CD45) 38 . Early passage (P2) were used for all experiments described below.…”
Section: Isolation and Culture Of Tdscsmentioning
confidence: 99%
“…Passage 2 TDSCs from were cultured to 100% con uence in a T75 ask then stimulated to differentiate into tenocytes by culturing for 7 days with complete medium supplemented with 25 ng/mL connective tissue growth factor (CTGF; PeproTech, Rocky Hill, NJ, USA) and 4.4 ng/mL ascorbic acid to promote extracellular matrix production 38 . Monolayer cell sheets were detached with 0.25% Trypsin and attached to the hook at the length of 10 mm to build a 3D TDSCs construct.…”
Section: Tenogenic Differentiation Assaymentioning
confidence: 99%